2022
DOI: 10.1038/s41467-022-29274-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for PoxtA-mediated resistance to phenicol and oxazolidinone antibiotics

Abstract: PoxtA and OptrA are ATP binding cassette (ABC) proteins of the F subtype (ABCF). They confer resistance to oxazolidinone and phenicol antibiotics, such as linezolid and chloramphenicol, which stall translating ribosomes when certain amino acids are present at a defined position in the nascent polypeptide chain. These proteins are often encoded on mobile genetic elements, facilitating their rapid spread amongst Gram-positive bacteria, and are thought to confer resistance by binding to the ribosome and dislodgin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 79 publications
2
61
0
Order By: Relevance
“…Our attempts to reconstitute HflXr-50S complexes in vitro were unsuccessful due to difficulties obtaining active soluble L. monocytogenes HflXr protein. Therefore, to generate homogenous L. monocytogenes HflXr-50S complexes for structural analysis, we employed an in vivo pull-down approach using the L. monocytogenes Δ hflXr strain overexpressing a C-terminally FLAG 3 -tagged HflXr protein, as used recently to generate ARE-ABCF–ribosome complexes ( 11 , 12 ). As a specificity control, we also performed the in vivo pull-down experiment using the L. monocytogenes Δ hflXr strain transformed with the empty pIMK3 plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…Our attempts to reconstitute HflXr-50S complexes in vitro were unsuccessful due to difficulties obtaining active soluble L. monocytogenes HflXr protein. Therefore, to generate homogenous L. monocytogenes HflXr-50S complexes for structural analysis, we employed an in vivo pull-down approach using the L. monocytogenes Δ hflXr strain overexpressing a C-terminally FLAG 3 -tagged HflXr protein, as used recently to generate ARE-ABCF–ribosome complexes ( 11 , 12 ). As a specificity control, we also performed the in vivo pull-down experiment using the L. monocytogenes Δ hflXr strain transformed with the empty pIMK3 plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…Since the initial description of the optrA gene, it and its many variants have been reported in several countries, revealing that it is more difficult to treat oxazolidinone-resistant bacteria ( Schwarz et al, 2021 ). Unfortunately, another ribosomal protection protein of the ABC-F family, poxtA , was reported in MRSA of clinical origin in 2018 ( Antonelli et al, 2018 ; Crowe-McAuliffe et al, 2022 ). The poxtA2 variant was also reported in 2021 ( Baccani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although oxazolidinone antibiotics have never been approved for use in livestock breeding, we often detect the transferable determinants of oxazolidinone resistance in enterococci isolated from animals used in food production ( Wang et al, 2020 ). Florfenicol is a phenicol compound that has broad spectrum antibacterial activity and few side effects and is used to treat respiratory and intestinal bacterial infections in animals used in food production ( Crowe-McAuliffe et al, 2022 ). It was reported that the abundance of oxazolidinone resistance genes in livestock feces was related to florfenicol residue ( Kim, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cfr and Cfr-like methylases confer resistance to five classes of antimicrobial agents, including phenicols, lincosamides, oxazolidinones, pleuromutilines, and streptogramin A (PhLOPS A phenotype) via the post-transcriptional methylation of the 23S rRNA [ 10 ]. The ABC-F proteins OptrA and PoxtA lead to a decreased susceptibility to phenicols and oxazolidinones (including tedizolid) by a ribosomal protection mechanism [ 11 ].…”
Section: Introductionmentioning
confidence: 99%